ARGUMENTASI HUKUM JAMINAN PRODUK HALAL - Siradj, Mustolih (Direktorat Jenderal Bimbingan Masyarakat Islam, 2015)
Abstract During this time most of the arguments in eliminating halal assurance system (SJH) is based on sectarian argument because the benefit is just come to a certain denomination, Islamic Ummah, on the other hand harming another religion. Textually could be phrase 'halal' is synonymous with the everyday vocabulary of the Muslims. But when we examined further, the problem of availability of halal products is not only a matter of Islamic Ummah, but also the problems of humanity. Because of the food consumed by the human race originated chain up to the birth of civilization is exist and specified quality. The halal food is kosher and thoyyib (good / nutritious) will give birth to a superior human generation. State in this matter has also been actively contribute to provide halal food products through a variety of regulatory instruments. This happened long before the enactment of Law No. 33 Year 2014 on Halal Product Guarantee (UU-JPH). There are many laws that spread such as the food laws, health laws, consumer protection laws and regulations under enactment reserved. Birth of UUJPH inspired by Islamic Shari'a becomes a confirmation of how the urgency of halal product assurance is a very urgent problem in addition to responding to the trend of global halal being implicated. By doing so, the consumer society are protected and inwardly feel comfortable consume and use products manufactured by businesses (manufacturers), both domestic and export.   Abstraksi Selama ini kebanyakan argumentasi dalam mengelominasi sistem jaminan halal (SJH) didasarkan pada argumentasi sektarian karena hanya menguntungkan ummat agama tertentu yakni ummat islam, di sisi lain merugikan ummat agama lain. Secara tekstual bisa frase ?halal? memang identik dengan kosa kata sehari-hari kaum muslim. Akan tetapi bila dicermati dan ditelisik lebih jauh masalah ketersediaan produk halal bukan hanya masalah ummat islam, akan tetapi persoalan kemanusiaan. Karena dari makanan yang dikonsumsi bermula rantai kehidupan ummat manusia hingga lahirnya peradaban bisa ada dan ditentukan kualitasnya. Makanan yang halal dan thoyyib (baik/bergizi) akan melahirkan generasi manusia yang unggul. Negara dalam persoalan ini juga telah aktif hadir berkontribusi menyediakan produk pangan halal melalui berbagai instrumen regulasi. Hal ini terjadi jauh sebelum lahirnya UU Nomor 33 Tahun 2014 tentang Jaminan Produk Halal (UU-JPH) ada banyak peraturan yang tersebar seperti pada undang-undang pangan, undang-undang kesehatan, undang-undang perlindungan konsumen dan peraturan-peraturan di bawah undang-undang. Lahirnya UUJPH yang terilhami oleh syariat islam menjadi penegas betapa urgensi jaminan produk halal merupakan persoalan yang sangat mendesak disamping merespon tren halal global yang sedang menggejala. Dengan begitu, masyarakat konsumen terlindungi dan secara batin merasa nyaman mengkonsumsi dan menggunakan produk yang diproduksi oleh pelaku usaha (produsen), baik domestik maupun ekspor.